Beyond Boundaries Essays on Theology, Dialogue, and Religion in Honor of Perry Schmidt-Leukel - Barbato, Melanie; Schneider, Mathias; Völker, Fabian (Waxmann, 2024)
Perry Schmidt-Leukel has made significant contributions to the academic study of religion and religious diversity through his innovative work in Theology and Religious Studies. In his publications, he has not only overcome apologetic barriers between Buddhism and Christianity and demonstrated the potential for mutual enrichment of various religious traditions in dialogue, but also championed a pluralist Theology of Religions. On this pluralist basis, Schmidt-Leukel has developed the vision of a theology beyond boundaries, which takes the form of interreligious discourse and draws on the rich resources and insights of the global history of religions. This Festschrift in honor of Perry Schmidt-Leukel on the occasion of his seventieth birthday brings together essays that constructively engage with his erudite and wide-ranging contributions to the fields of Theology of Religions, Interreligious Theology, Philosophy of Religion, Buddhist and Religious Studies, Buddhist-Christian Relations, and Interreligious Dialogue
Keywords: Theology of Religions; Interreligious Theology; Philosophy of Religion; Religious Studies; Interreligious Dialogue; Buddhism; Buddhist Studies; religious diversity; pluralism; Theologie der Religionen; Interreligiöse Theologie; Religionsphilosophy; Religionswissenschaft; Interreligiöser Dialog; Buddhismus; religiöse Vielfalt; Pluralismus